DAMPAK PERJODOHAN ANAK TERHADAP RUMAH TANGGA DI DESA PACCELLEKANG KECAMATAN PATTALLASSANG KABUPATEN GOWA (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2021)
The journal that was made aims to describe the impacts of matchmaking on households in Paccellekang village, Pattallassang sub-district, Gowa regency. The explanation of this journal is obtained from the results of literature studies from reading various articles, books, theses, and direct interviews with children who feel the impact of matchmaking by their parents. Many parents make matchmaking with their children, when they were still at the education level and also when they were underage, from various impacts that often occur, namely domestic violence (KDRT), as well as economic limitations resulting in the divorce between children who are matchmaking. The results of the analysis show that child matchmaking is very common today.